RELATIONSHIPS WITHIN THE TRADITIONAL GIDAR FAMILY (NORTHERN CAMEROON) ON THE BASIS OF LOCAL ORATURE - Jarosław Różański (Forum Teologiczne, 2022)
Common to all of Africa is the attitude of the family towards procreation. It can safely be said that in the Gidar understanding, the family is more a community of mother and father than of husband and wife. The father was the unquestioned authority and traditional head of the family. The decisive voice was his, and everyone owed him absolute obedience. The woman clearly felt her inferiority, which was approved by all and confirmed by dozens of everyday, traditional rules of life. Children were a great gift, and their absence was a sign of a curse. Therefore there was no occurrence of orphans, in the sense of children being left without caregivers. Orphans were never abandoned; there was always someone who would take care of them. This does not mean that their life was an easy one. The deceased ancestors were still involved in the daily events of family life, especially at times of sowing and harvesting, initiations and of marriages.